Beckman automobile engine testing equipment - Karjalas' Photo Vision
These pieces of equipment include an Ignition System Tester (right) and an HC/CO/CO2 tester (center). The instrument on the left is unidentified. The IST was also known as an Engine Scope Tester. The HC/CO/CO2 Tester detects pollutants in the exhaust from vehicles with combustion engines.
Keywords: Scientific apparatus and instruments; Automobiles--Ignition; Automobiles--Motors--Exhaust gas--Measurement; Beckman Instruments, Inc.